CFD Optimization Of Building Glazed Cladding In Order To Achieve Thermal Comfort And Achieve Energy Saving - Armando Macuacua, Florivaldo Daniel (IRC, 2020)
Double skin façade (DSF) have been widely implemented by new and existing buildings in the market to improve thermal comfort at expense of very low energy demands. DSF has proved to reduce the cooling loads of 30% in buildings that were not conceived with DSF and about 50 % in new buildings. This project aimed to study the Space size between the two façade which has not been optimized and use the structural support as fins to increase heat exchange rate of between the cavity air and outer skin. A building of 2 floors with glazed external façade is used to simulate the impact of sun in DSF. Using Ansys Computer Fluid Dynamics (CFD) analyses the impact of varying the cavity size while using two design of fins.